The Influence of Leverage, Financial Distress, Management Strategy and Company Growth on Audit Opinions - MUSLIH, Robet; HERMANTO, Hermanto (PT Keberlanjutan Strategis Indonesia, 2024)
This study aims to analyze various factors that influence auditors in issuing going concern opinions on manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange. During the period 2019 to 2024. The main focus of the study is directed at five independent variables, namely Leverage, financial distress, management strategy, company growth, and company size. A quantitative approach is used in this study with the logistic regression analysis method. The research sample consists of 49 companies with a total of 294 annual observations collected from audited financial statements. Based on the analysis results, the five variables studied together are able to build a significant prediction model for the issuance of going concern opinions by auditors. Partially, management strategy as measured by Price to Book Value (PBV) is proven to have a positive and significant influence on the likelihood of a company obtaining an auditor's going concern opinion. It is also influenced by several factors, one of which is company size which is proven to have a significant impact in the determination process, but in a negative direction. Meanwhile, Leverage, financial distress, and company growth do not show a statistically significant influence, although they remain contextually relevant in the context of audit risk evaluation. These findings provide a significant contribution to enhancing auditors' understanding of the factors influencing business continuity. This research also offers practical implications for corporate management in improving the quality of strategic decision-making and risk management to maintain business continuity amidst complex economic dynamics.